Формування засобів маркетингових комунікацій машинобудівних підприємств - Чернобровкіна, Світлана Віталіївна (Національний технічний університет "Харківський політехнічний інститут", 2020)
Дисертація на здобуття наукового ступеня кандидата економічних наук за спеціальністю 08.00.04 – економіка та управління підприємствами (за видами економічної діяльності). – Національний технічний університет «Харківський політехнічний інститут», Харків, 2020. В дисертації узагальнено наукові основи, проаналізовано сучасний стан та рівень маркетингових комунікацій машинобудівних підприємств, а також обґрунтовано найбільш перспективні напрями їх удосконалення. Розроблено модель впливу засобів маркетингових комунікацій на фінансовий результат промислового підприємства за рахунок складових комунікативного та економічного ефекту. Побудовано профілі поточної та цільової PR-активності машинобудівних підприємств. Запропоновано визначення показника комунікативності машинобудівних підприємств. Розраховано показники комунікативності обраних машинобудівних підприємств. Запропоновано методичний підхід до формування засобів маркетингових комунікацій машинобудівних підприємств за тривимірною моделлю в залежності від галузі, продукції машинобудування та цільової аудиторії. Зроблено оптимізаційне моделювання витрат на засоби маркетингових комунікацій на прикладі машинобудівних підприємств України, де враховано показники, які характеризують збільшення чистого фінансового результату діяльності підприємства.

Thesis for granting the Degree of Candidate of Economical sciences in specialty 08.00.04 – economy and management of the enterprises (by types of economic activity). – National Technical University «Kharkiv Polytechnic Institute», Kharkiv, 2020. The thesis is devoted to the research of the actual scientific problem of marketing communications of industrial enterprises. The scientific foundations are generalized, the current state and level of marketing communications of machine-building enterprises is analyzed, and the most promising directions of their improvement are substantiated. Due to the selection and analysis of key terms in the work, the main scientific approaches to the interpretation of such concepts as marketing communications, their impact on the financial result of the enterprise, optimized costs for marketing communications, etc. are systematized. Accordingly, it is emphasized on the need to understand and understand the objectives of marketing communications as an important tool for the development of machine-building enterprises. The classification of communication facilities of industrial enterprises is proposed: the section of communications is shown on the traditional ones, which require significant financial investments from the enterprise, and non-traditional, which do not require significant investments from the enterprise. The model of influence of marketing communications measures on the financial result of the industrial enterprise due to the components of the communicative and economic effect is proposed, which allows to trace the influence of each measure of marketing communications on the financial result of the industrial enterprise The list of expenses for organization of communication actions, factors of influence and criteria for determining the effect of measures is summarized. The analysis of activity of domestic machine-building enterprises is made. The structure of sold products by groups of enterprises of machine building of Ukraine, level of their profitability, volumes of unrealized products is presented. The research of main measures of marketing communications of the enterprises of machine building of Ukraine has been carried out. The profiles of current and desired PR activity of machine-building enterprises are built The dynamics of expenses for sales of machine-building enterprises of Ukraine is shown, and the relationship between sales and financial results of the enterprise is shown. The definition and calculation of the communicative index of machine-building enterprises is proposed. The indicators of communicativeness of selected machine-building enterprises are calculated. The methodical approach to formation the means of marketing communications of the machine-building enterprises on three-dimensional model is offered depending on branch, production of mechanical engineering and target audience. The optimization modeling of marketing communications costs is made on the example of machine-building enterprises of Ukraine, which takes into account the indicators that characterize an increase in the net financial result of the enterprise, namely: an increase in the market share, an increase in turnover, an increase in the brand equity of a machinebuilding enterprise, which allows determining the optimal level of marketing communications expenses for the enterprise. The investigated companies received the only optimal solution for Pareto, which provides the optimal amount of expenses for marketing communications in terms of its net financial result, market share, sales volumes and brand equity. The methodical approach to formation of means of marketing communications of the machine-building enterprises on three-dimensional model depending on branch, production of mechanical engineering and target audience is offered.
Formation of marketing communications for machinebuilding enterprises
Keywords: автореферат дисертації; маркетингові комунікації; машинобудівні підприємства; фінансовий результат; засоби комунікацій; реалізована продукція; PR-активність підприємства; профілі PR-активності; комунікативність підприємства; тривимірна модель; комунікативний ефект; економіко-математичне моделювання витрат; ефективність комунікативних витрат; marketing communications; machine-building enterprises; financial result; means of communication; sold products; PR-activity of enterprise; profiles of PR-activity; communicativeness of enterprise; three-dimensional model; communicative effect; economic-mathematical modeling of expenses; efficiency of communicative expenses; 339.138